Charter and Ordinances of the City of La Crosse, with the Rules of the Common Council, at 202, Ordinance no. 27 (1888) - (:unkn) unknown (General Publisher, 1881)
No person shall fire or discharge any cannon, gun, fowling piece, pistol or firearms of any description, or fire, explode or set off any squib, cracker or other thing containing powder or other combustible or explosive material, or set off or exhibit any fireworks within the limits of the city of La Crosse
--
Keywords: DISCHARGE